2013
DOI: 10.1016/j.cell.2013.10.043
|View full text |Cite|
|
Sign up to set email alerts
|

ATR Prohibits Replication Catastrophe by Preventing Global Exhaustion of RPA

Abstract: ATR, activated by replication stress, protects replication forks locally and suppresses origin firing globally. Here, we show that these functions of ATR are mechanistically coupled. Although initially stable, stalled forks in ATR-deficient cells undergo nucleus-wide breakage after unscheduled origin firing generates an excess of single-stranded DNA that exhausts the nuclear pool of RPA. Partial reduction of RPA accelerated fork breakage, and forced elevation of RPA was sufficient to delay such "replication ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
659
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 769 publications
(695 citation statements)
references
References 43 publications
30
659
2
4
Order By: Relevance
“…Toledo and colleagues recently reported that the ATR/CHK1 signaling axis maintains the integrity of stalled replication forks in part by regulating the available pool of RPA to coat exposed ssDNA (13). Under conditions of replication stress, inhibition of ATR and CHK1 resulted in depletion of the nuclear RPA pool, breakage of stalled forks, and fragmentation of chromosomes.…”
Section: Ly2606368 Causes Replication Catastrophementioning
confidence: 99%
See 3 more Smart Citations
“…Toledo and colleagues recently reported that the ATR/CHK1 signaling axis maintains the integrity of stalled replication forks in part by regulating the available pool of RPA to coat exposed ssDNA (13). Under conditions of replication stress, inhibition of ATR and CHK1 resulted in depletion of the nuclear RPA pool, breakage of stalled forks, and fragmentation of chromosomes.…”
Section: Ly2606368 Causes Replication Catastrophementioning
confidence: 99%
“…Another hallmark of replication catastrophe caused by loss of ATR/CHK1 origin control is depletion of the pool of RPA protein available to protect ssDNA at replication forks (13). This is due to the excess of open replication forks with exposed ssDNA and can be measured by high-content image analysis of the coaccumulation of RPA2 protein and phosphorylated H2AX (S139) on the chromatin of each cell.…”
Section: Ly2606368 Causes Replication Catastrophementioning
confidence: 99%
See 2 more Smart Citations
“…In their absence, stalled forks persist and additional backup origins are fired, leading to an exhaustion of dNTP pools and a further accumulation of non-progressive forks. When the amount of ssDNA exceeds the pool of available RPA, and by yet not fully understood mechanisms, forks collapse leading to the generation of DNA double strand breaks (DSB) [7]. The lack of checkpoint activation in these cells allows them to progress to mitosis with unreplicated chromosomes leading to death by mitotic catastrophe.…”
Section: Introductionmentioning
confidence: 99%